Identification of KIR3DL1*0150208 using long-range sequence-based techniques. - Wang, L; Xu, K; Dong, T; Rowland-Jones, S; Yindom, L (2014)
KIR3DL1*0150208 possesses five point mutations: 3037G>A, 4115A>G, 6053G>C, 8034A>G, and 9446T>C compared to KIR3DL1*0150201. © 2014 John Wiley and Sons A/S.